P214 Preliminary results: driving improvements in disease outcomes for rheumatoid arthritis patients using remote disease activity monitoring via smartphone app. (20th April 2020) - MacBrayne, Amy C. B; Pott, Jason; Petrovic, Vladan; Pitzalis, Costantino; Humby, Frances
Abstract: Background: Biologic dose tapering in RA is attractive due to the reduced costs, and potentially reduced risks, although there is a significant risk of disease flare. Capturing flares can be challenging within current NHS clinic frameworks with limited capacity. Remote disease monitoring through patient collected joint counts has previously been demonstrated to be feasible and reliable. BioT-app was co-designed by clinicians and patients using an iterative collaborative design process. It functions as a medication tracker and to remotely collect patient recorded joint counts. The aim of this study was to establish the validity, acceptability, and feasibility of BioT-app as a monitoring tool to support biologic dose tapering for RA patients. Methods: 30 RA patients on injectable biologics were recruited to a prospective, observational study and followed for 6 months. Those enrolled in the app attended for joint count training, with a second remote assessment 1 week later to confirm patient reproducibility. Patients submitted tender & swollen joint counts, and global VAS scores in line with their biologic dosing schedule. DAS28 scores were completed following entry of ESR/CRP levels. Patients observed to be in persistent low disease activity (DAS<3.3 for >6/12) were offered the opportunity to taper their biologic. Significant flares in DAS28 (>1.2 or any score >5.1) triggered contact by the clinical team and early face to face review offered. Results: Thirty patients were enrolled into the study. One patient was withdrawn due to inability to submit their initial test-tracking DAS score. The mean age was 56.7 years (range 28-81), 56.7% were female; 86.7% were sero-positive (ACPA and/or RF). Ethnicity was 60% White British: 27% South Asian & 13% White Other. Twenty patients (69%) were on TNFi (8 etanercept; 6 certolizumab; 3 adalimumab; 3 golimumab), and nine (31%) were on a non-TNFi biologic (6 tocilizumab; 3 abatacept). 48% of patients were on a weekly schedule, so submitted DAS scores weekly; 35% fortnightly; 17% monthly. Mean baseline DAS score was 2.43, mean initial patient submitted DAS was 3.09. One patient underwent re-training based on their initial self-submitted DAS. 12/31 (41%) of patients completed every DAS score; 8/31 (28%) completed >80% scores; 5/31 >60%. Four patients (13.8%) input less than 50% of their scores. Four patients' biologics were tapered. Two patients flared, defined by DAS-28 increase >0.6 within 3 weeks, and returned to their baseline regimen. Two patients remained on a tapering regimen. One patient was switched back to bio-originator following submission of a DAS>5.1, confirmed by physician joint count during face-to-face consultation. Conclusion: Preliminary results suggest that BioT-App is a reliable and acceptable tool which facilitates enhanced remote monitoring and rapid response to changes in disease activity scores for patients on biologic therapy, including those undergoing dose tapering. Disclosures: A.C.B. MacBrayne None. J. Pott None. V. Petrovic None. C. Pitzalis None. F. Humby None.